Cyber harassment: hate speech with news spread hoax death via the tiktok account @p*********a - Sri Narti; Yanto Yanto (The International Journal of Politics and Sociology Research, 2023)
Social media TikTok is a means of communication for today’s society. The content presented on TikTok varies, from positive to negative, so it reaps a lot of comments from netizens. Cyber harassment in this research is hate speech dissemination of news hoax artist death and netizen comments. This study aims to discuss hate speech spreading hoax news as a form of Online Gender-Based Violence and social interaction with netizens in the TikTok comments column. The data sources come from comments from TikTok users while the data collection techniques are through observation, documentation, and literature studies. Furthermore, the data were analyzed using social identity theory. The findings in the study showed three forms of online gender-based violence. First, the slanderous hate speech of the account owner for the victim. Second, hate speech netizens ridicule and annoyance for the account owner with language style satire. Third, hate speech netizen humiliation and dropping of social identity for victims with sarcasm style. Netizens interact through the comments column with their group identity and the communication encountered is the use of non-standar language. Form of violence such as anger, annoyance, curiosity, and even humiliation. The solution offered apply ethics, morals, and empathy in social media.